Detecting natural fractures with ground penetrating radar and airborne night-thermal infrared imagery around Old Faithful Geyser, Yellowstone National Park, USA. (May 2020) - Jaworowski, Cheryl; Lynne, Bridget Y.; Heasler, Henry; Foley, Duncan; Smith, Isaac J.; Smith, Gary J.
Highlights: Ground penetrating radar around Old Faithful Geyser detected intersecting fractures. Thermal infrared trends are consistent with "blind" fractures. Thermal infrared trends are consistent with mapped Old Faithful fractures. Ground penetrating radar detected fractures in Yellowstone National Park. Combined tools contribute new information about the shallow hydrothermal system. Abstract: Both surface and shallow (∼3 m depth) subsurface natural fractures exist around the siliceous sinter cone of Old Faithful Geyser in Yellowstone National Park. Surface fracture trends identified using night-thermal infrared (TIR) imagery are consistent with previously mapped fault and fracture trends in the Upper Geyser Basin and Old Faithful area. An April 2015 ground penetrating radar (GPR) survey of the Old Faithful Geyser cone detected similar "blind" subsurface fracture trends around the siliceous sinter cone of Old Faithful Geyser. Intersecting NE and NW as well as WNW and ENE trends in the shallow subsurface provide potential fracture pathways for the flow of hydrothermal fluids around Old Faithful Geyser. Both the TIR and GPR techniques contribute new information on the permeable pathways around Old Faithful Geyser.